1995
DOI: 10.1073/pnas.92.8.3166
|View full text |Cite
|
Sign up to set email alerts
|

Temporally distinct accumulation of transcripts encoding enzymes of the prechorismate pathway in elicitor-treated, cultured tomato cells.

Abstract: The accumulation of phenylalanine-derived phenolic compounds is a well-known element of a plant's defense in response to pathogen attack Phenylalanine, as well as the other two aromatic amino acids, tyrosine and tryptophan, is synthesized by way of the shikimate pathway. The first seven steps of the shikimate pathway (the prechorismate pathway) are common for the biosynthesis of all three aromatic amino acids. We have studied transcript levels of six genes-i.e., two 3-deoxy-D-arabino-heptulosonate 7-phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 27 publications
6
69
2
1
Order By: Relevance
“…In agreement with the latter possibility, G€ orlach et al (1995) suggested that the increased demand for phenylalanine in the phenylpropanoid pathway after elicitor treatment increased de novo synthesis of phenylanine biosynthesis. 38 Our results together with Slisz's observation suggested that phenylalanine may play an important role in citrus response to CLas.…”
Section: Discussionmentioning
confidence: 48%
“…In agreement with the latter possibility, G€ orlach et al (1995) suggested that the increased demand for phenylalanine in the phenylpropanoid pathway after elicitor treatment increased de novo synthesis of phenylanine biosynthesis. 38 Our results together with Slisz's observation suggested that phenylalanine may play an important role in citrus response to CLas.…”
Section: Discussionmentioning
confidence: 48%
“…The aromatic precursor HGA is derived from prephenate or Tyr, both products of the shikimate pathway (Threlfall and Whistance, 1971;Fiedler et al, 1982;Lopukhina et al, 2001;Sandorf and Hollander-Czytko, 2002). In plants, the shikimate pathway has been shown to be regulated at the transcriptional level and globally up-regulated during biotic and abiotic stresses (Gorlach et al, 1995;Herrman and Weaver, 1999;Diaz et al, 2001). Thus, the shikimate pathway may provide an increased pool of prephenate that is at least partially used for elevated tocopherol synthesis in stressed plants.…”
Section: Discussionmentioning
confidence: 99%
“…DAHP synthase catalyzes the entry step of the shikimate pathway and in microorganisms is regulated transcriptionally and is also subjected to feedback regulation by Phe at the enzyme level (Bentley, 1990;Herrmann and Weaver, 1999). In plants, DAHP synthase genes are transcriptionally regulated and induced in response to various environmental stimuli (Dyer et al, 1989;Keith et al, 1991;Gö rlach et al, 1995). At the enzyme level, however, all plant DAHP synthases examined to date are insensitive to Phe (Huisman and Kosuge, 1974;Suzich et al, 1985;Herrmann, 1995).…”
Section: Regulation Of the Shikimate Pathway Leading To Phe Biosynthesismentioning
confidence: 99%